Biological rhythms and vector insects - Mirian David Marques (Memorias do Instituto Oswaldo Cruz, 2013)
The adjustment of all species, animals and plants, to the Earth’s cyclic environments is ensured by their temporal organisation. The relationships between parasites, vectors and hosts rely greatly upon the synchronisation of their biological rhythms, especially circadian rhythms. In this short note, parasitic infections by Protozoa and by microfilariae have been chosen as examples of the dependence of successful transmission mechanisms on temporal components.